Incidence, causes and predictors of unplanned hospital readmission after percutaneous coronary intervention. (25th November 2020) - Biswas, S; Dinh, D; Lucas, M; Duffy, S.J; Brennan, A; Liew, D; Cox, N; Nadurata, V; Reid, C.M; Lefkovits, J; Stub, D
Abstract: Background: Unplanned hospital readmissions post-percutaneous coronary intervention (PCI) result in a significant burden to the healthcare system and adverse patient outcomes. Understanding factors associated with 30-day readmission rates may help to reduce this burden. Data linkage of clinical quality registry data with routinely collected administrative datasets may assist in overcoming resource constraints that limit collection of follow-up data but is currently under-utilised worldwide. Objective: To determine the incidence of, and factors associated with unplanned hospital readmissions in the first 30 days following PCI. Methods: We prospectively collected data on 28, 488 patients undergoing PCI between January 2013 and December 2018, who were enrolled in a multi-centre PCI registry. Data linkage to government administrative datasets was used to determine whether patients had an unplanned readmission within 30 days of PCI, the number of admissions prior to PCI and primary reason for readmission (as recorded by the International Classification of Diseases, 10th revision, Australian modification (ICD-10-AM) diagnosis codes). Patients were then divided into 3 groups: those who had 1 or more unplanned readmissions for primarily cardiac issues, those who those who had 1 or more unplanned readmissions for primarily non-cardiac issues, and those who were not readmitted, and compared for baseline, procedural and in-hospital care characteristics. Results: In total, 3, 059 patients (10.7%) had an unplanned hospital readmission within 30 days of PCI, of which, 1, 848 patients (60.4%) were readmitted for primarily cardiac diagnoses. Independent predictors of both 30-day cardiac and non-cardiac readmissions were female sex, having >1 admission in the 12 months prior to PCI, acute coronary syndrome presentation, having any in-hospital complication and being discharged on an oral anticoagulant (all p<0.05). A stepwise increase in readmission risk was observed with increasing number of admissions from 1 to >4 admissions in the 12 months prior to PCI. Presentation with cardiogenic shock (p=0.04), having an unsuccessful PCI (p=0.02) and left ventricular systolic dysfunction (p=0.02) were independent predictors of cardiac readmissions but not non-cardiac readmissions. Conversely, age >60 years (p<0.001) and history of diabetes mellitus (p=0.02) were found to be independent predictors of non-cardiac readmissions only. Conclusion: Thirty-day unplanned hospital readmissions after PCI pose a significant burden to the health system. Most readmissions are primarily due to cardiac diagnoses. The most important predictive factor for both cardiac and non-cardiac readmissions appears to be the number of hospital admissions in the 12 months prior to PCI. This is valuable information for health administrators as treatment and discharge policies, and outpatient follow-up timetables may need to be tailored to patients at high risk for readmission following PCI. Funding Acknowledgement: Type of funding source: None